Forestry Education at Toronto - Sisam, John W. B. (Book collections on Project MUSE., 1961)
Dean Sisam has traced the history of the Faculty of Forestry at the University of Toronto from its establishment over fifty years ago to the present day. The first half of his survey is chronological. The second half is analytical.